Geochemistry of siltstones from the Permian Corumbatai Formation from the Parana Basin(State of Sao Paulo, Brazil): Insights of provenance, tectonic and climatic settings - Montibeller, Cibele Carolina [UNESP]; Beltran Navarro, Guillermo Rafael [UNESP]; Zanardo, Antenor [UNESP]; Rohn, Rosemarie [UNESP]; Del Roveri, Carolina; Rocha, Rogers Raphael da [UNESP]; Conceicao, Fabiano Tomazini da [UNESP] (Elsevier B.V., 2020)
The Corumbatai Formation is a Permian sedimentary unity comprising siltstones, claystones and very fine sandstones, deposited above calcific shales, bituminous shales and dolomitic limestones from the Irati Formation, indicating severe changes in tectonic and climatic conditions in a short span during the evolution of the Parana Basin. Through geochemical analysis of major elements, it is possible to observe that some characteristics of the Corumbatai Formation indicate that the climate on the period of deposition was arid or semiarid, with low contribution of fluvial and pluvial waters, and that, as expected, the chemical signature of the sediments are similar to the adjacent orogenic belts, despite that no tectonically active areas or magmatic arcs were registered in the surroundings of the Parana Basin during Permian. These aspects suggest that the aridization of the Pangea Supercontinent started earlier than considered so far, and that the source areas for this sedimentary unity most probably were distant from the basin, being that the main possible transportation process of the detritic grains should be aeolian.
Keywords: Lithogeochemistry; Pangea; Intracratonic basin; Gondwana I Supersequence; Major elements geochemistry; Sedimentary geochemistry